“The Beginnings of Armenian Professional Vocal Art. Haikanush Danielyan”. - Bazinyan Арменуи Сережаевна (Musical Armenia, 2021)
The article presents the work of Haikanush Danielyan, one of the founders of the Armenian school of singing, who created the traditions of the Armenian vocal art. H. Danielyan is introduced as a bright individual who made a significant contribution to the development of both republican and Soviet opera and chamber vocal schools. Along with performing, Danielyan was involved in teaching as a professor at Yerevan Komitas State Conservatory.